Diachronic analysis of coloronyms in French scientific-chemical discourse: semantic & structural-syntactical aspects - M. V. Volkova (Дискурс профессиональной коммуникации, 2019)
This paper is devoted to the structural-semantic evolution of French coloronyms in scientific chemical discourse. The author analyzes the definition of scientific chemical discourse and its distinctive functional-linguistic characteristics, such as aim, agents, clients, functional space, linguistic peculiarities. Coloronyms are described as colour terms, promoting the enrichment of the scientific-chemical communication. Semantic analysis of vast empirical material helps to create the classification of coloronyms based on their etymology (coloronyms of animal origin, mineral origin, synthetic origin, metallic origin). The author carries out meticulous diachronic analysis of coloronyms in French scientific chemical discourse in the XIXth – XXth centuries with regard to the structural and syntactical aspects.French scientific chemical discourse is a special sphere of communication which is actively developing and possesses its own set of peculiar functional-linguistic parametres. With the help of diachronic analysis of the scientific-chemical texts of the XIXth and XXth centuries the author reveals structural-syntactical transformations, e.g. simplification of structural models, the tendency to the diversity of syntactical roles of coloronyms.